Best Answer

x4 - 1.

We can not "solve" this as we have not been told the value of x. However, we can simplify this expression:

We have an x and a minus x here which will cancel out. Likewise the x2 and x3 will cancel out with the -x2 and -x3 respectively. This therefore leaves us with just x4 - 1.

User Avatar

Wiki User

12y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: How do you solve x-1 plus x2-x plus x3-x2 plus x4-x3?
Write your answer...
Still have questions?
magnify glass
Related questions

What is the answer to 2x plus 5 plus x2x-1 plus 2x plus 4?

x equals 4

What is the combined term of 2x plus x?

2x+x2x = x+xso 2x+x isx+x+x = 3x

What is x2x-1 multiplied by x?


Nine less than twice a number is equal to the number what is the number?

The answer is 9.You solve it as:2x-9=x2x-x=9x=9

What does 2x 8 x2x 15?


What are the coefficient of 4 x2x 6?

what are the coefficient of this number -8a+2=13

If 3x-111 what is the value of x2x?


What is 4-x2x-5?

If you mean: 4-x = 2x-5 then the value of x is 3

What is 3x - 1 11 what is the value of x 2 x?

-if3X-1=11,what is the value of X^2+X?

What is x if 6 x-2 -4x equals 16 space is paraenthesis?

6(X-2)-4X=16before you can solve for x you first have to bring the x terms togetherand to do that you distribute the 6 to remove the parenthesis6x-(6)2-4x=16 turns into6x-12-4x=16because -4x and 6x are terms of the same degree they can be added togetheryoull get2x-12=16now solve for x2x-12=16 get x term alone by addind 122x=28 now divide 2x=14

How do you simplify e to the 2xlnx power?

e2xlnx = x2x since ln x is the opposite to e so you just leave the x from the log and the rest of the exponent stays the same.

How do you find maximum height when working with quadratic equations?

In a quadratic equation, the vertex (which will be the maximum value of a negative quadratic and the minimum value of a positive quadratic) is in the exact center of any two x values whose corresponding y values are equal. So, you'd start by solving for x, given any y value in the function's range. Then, you'd solve for y where x equals the middle value of the two x's given in the previous. For example:y = x24 = x2x = 2, -2y = (0)2y = 0Which is, indeed, the vertex of y = x2